The Global Issues of The Islamic Economic System: Study Of Islamic Philantrophy (Ziswaf) as a Strategy For 2023 Recession In Indonesia - Mochammad Harun Rosyid (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
Russia's Ukrainian conflict is not only a concern internationally but also a problem for the international market due to the threat of a food and energy crisis Moreover, the two countries are the world's largest producers and exporters of oil gas, and wheat. This resulted in a global recession, which was characterized by a decrease in economic activity, increased inflation, and weak economic growth. The threat of economic recession hits various countries because they cannot pay production costs and tend to have layoffs while increasing the national unemployment rate. This paper offers the instrument of Islamic philanthropy (Ziswaf) the means to deal with a global economic recession. Social funds (Ziswaf) are widely used for humane programs, especially for the economically weak, both consumptive and productive. This paper uses a narrative method of quantifiable research with literature obtained from books, newspapers, and other information media. In the paper, evidence of previous research will also be given as evidence that Ziswaf can become a strategy as well as a solution to face the 2023 economic recession. Moreover, if the Ziswaf funds are distributed properly and fairly, undoubtedly the unemployment and poverty rates are easily overcome.